(36-16* x)*4=160 (3742-x):54=69 (3742+x):54=69

(36-16* x)*4=160 (3742-x):54=69 (3742+x):54=69
Гость
Ответ(ы) на вопрос:
Гость
(36 - 16 * х) * 4 = 160 36 - 16 * х = 160 : 4 36 - 16 * х = 40 16 * х = 36 - 40 16 * х = - 4  х = - 4 : 16 х = - 0,25 Проверка: (36 - 16 * (-0,25)) * 4 = 160                   (36 + 4) * 4 = 160                    40 * 4 = 160                    160 = 160 (3742 - х) : 54 = 69 3742 - х = 69 * 54 3742 - х = 3726 х = 3742 - 3726 з = 16 Проверка: (3742 - 16) : 54 = 69                   3726 : 54 = 69                   69 = 69 (3742 + х) : 54 = 69 3742 + х = 69 * 54 3742 + х = 3726 х = 3726 - 3742 х = - 16 Проверка: (3742 - 16) : 54 = 69                    3726 : 54 = 69                    69 = 69                 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы